Pandemic's silver lining. Issue 1 (31st December 2022) - Ferrara, Fortunato; D'Angelo, Sara; Erasmus, M. Frank; Teixeira, André A.; Leal-Lopes, Camila; Spector, Laura P.; Pohl, Tom; Fanni, Adeline; Cocklin, Simon; Bradbury, Andrew R. M.
ABSTRACT: The intense international focus on the COVID-19 pandemic has provided a unique opportunity to use a wide array of novel tools to carry out scientific studies on the SARS-CoV-2 virus. The value of these comparative studies extends far beyond their consequences for SARS-CoV-2, providing broad implications for health-related science. Here we specifically discuss the impacts of these comparisons on advances in vaccines, the analysis of host humoral immunity, and antibody discovery. As an extension, we also discuss potential synergies between these areas. Abbreviations: CoVIC: The Coronavirus Immunotherapeutic Consortium; EUA: Emergency Use Authorization